Editorial Discource Daily Suara Merdeka: Cohesion and Coherence Studies (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Suara Merdeka newspaper is a daily that is trusted by the people of Central Java as a source of current information on conditions and policies in Central Java. The author finds variations in the use of cohesion and coherence markers, whose function is as a means of connecting one another to form a link. The objectives of this research are finding and describing the forms of cohesion of the Suara Merdeka newspaper editorial, finding and describing the forms of coherence that are used in the editorial discourse of Suara Merdeka newspaper, describe the function of cohesion and coherence in the editorial discourse on Suara Merdeka newspaper. The data in this research are fragments of the Suara Merdeka daily editorial. The note-taking technique follows the method of data collection by listening. While the data analysis technique used is the basic technique for direct elements and advanced techniques behind the technique. Thus the important findings of this research showed that the lexical cohesion used in the Merdeka Voice Editorial Discourse was repetition, synonymy, antonymy, collocation, and hyponymy. The dominant reps used are Epizeuskis, and Tautote reps, coherence used in the Suara Merdeka daily editorial include causality, causality, causality, comparative relations, time additives, and conclusions. However, what dominates the most is the causal relationship, the function of cohesion and coherence in the Suara Merdeka editorial discourse is to make the reader understand the implied and explicit message of the writer and as a marker for combining sentences and paragraphs. This research is useful to add insight to the development of linguistics related to discourse analysis, especially cohesion and coherence.